Nephrotoxicity and Kidney Fibrosis Due to Gentamicin in Wistar Rats - Lusiana, Evi; Saleh, Irsan; Sinaga, Ernawati; Hafy, Zen (RSUP Dr. Kariadi, 2023)
Background : Gentamicin is an aminoglycoside used as a treatment for various infections. One of the side effects reported on the use of gentamicin is nephrotoxic. However, there are still many uses of gentamicin that have not been precisely indicated. Objective : To analyze the nephrotoxic effects leading to renal fibrosis due to gentamicin induction in Wistar rats. Methods : This research is an in vivo experimental study, pre- and post-test control group design, conducted in September and October 2022 at the Animal House Laboratory of the Faculty of Medicine, Sriwijaya University, and the Palembang Health Laboratory Center. There were 4 treatment groups: Group I, placebo; Group II, gentamicin-induced (GIG I) at 80 mg/kgBW; Group III, gentamicin-induced (GIG II) at 120 mg/kgBW; and Group IV, gentamicin-induced (GIG III) at 240 mg/kgBW. Gentamicin was administered intraperitoneally for 7 days, to 8 Wistar rats per group. Blood was taken from all Wistar rats in each group on days 0, 3, 7, and 14. The results of the study were tested for normality with the Shapiro-Wilk test and homogeneity with the Levene's test. The ANOVA test and the Post-Hoc test were used to conduct the analysis. Results : Induction of gentamicin in the GIG I and GIG II groups was significant in increasing the mean creatinine and urea levels on day 0 and day 14 of treatment (p<0.05). In the GIG III group there was a 50% mortality in experimental animals showing a Lethal dose of 50 (LD50) at that dose. Conclusion : GIG I and GIG II have significant nephrotoxic effects in increasing creatinine and urea levels which lead to renal fibrosi.